The American 1890s : A Cultural Reader - Dawson, Melanie, 1967-; Smith, Susan Harris (Book collections on Project MUSE., 2000)
An anthology of articles from periodicals of the 1890s, chosen to reflect various aspects of American culture during the last fin-de-siecle.